Tuberculin Skin Test and T-SPOT.TB for Latent Tuberculosis Infection detection in healthcare workers - Yusup Subagio Sutanto; Paulus Arka Triyoga; Harsini Harsini; Reviono Reviono; Hendra Kurniawan (Jurnal Kesehatan Masyarakat, 2023)
Healthcare Workers (HCWs) have a higher risk of getting Tuberculosis (TB) than the general population. This study analyzed effectiveness of Tuberculin Skin Test (TST) and T-SPOT.TB for detection prevalence of Latent Tuberculosis Infection (LTBI) among HCWs and the correlation between work locations and HCW duties. A trial study with a cross-sectional study design in Dr. Moewardi Hospital, Surakarta, in December 2018. The sampling technique used consecutive sampling with 30 subjects. Data analysis was performed using SPSS 21 for Windows. The appropriate levels of TST and T-SPOT indicated substantial TB (K = 0.603, p 0.001). The sensitivity and specificity of T-SPOT.TB with close contact was 60% and 86.7%. The sensitivity and specificity of TST with close contact were 33.3% and 93.3%. T-SPOT.TB was a significant correlation between the work location, the pulmonary care ward r = 0.436 and p = 0.008 (p 0.05). T-SPOT.TB has a slightly better sensitivity than TST.